2020
DOI: 10.1002/mp.14057
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of radiation‐induced malfunction for cardiac implantable electronic devices (CIEDs)

Abstract: Purpose Cardiac implantable electronic devices (CIEDs) were believed to possess a tolerance dose to malfunction during radiotherapy. Although recent studies have qualitatively suggested neutrons as a cause of malfunction, numerical understanding has not been reached. The purpose of this work is to quantitatively clarify the contribution of secondary neutrons from out‐of‐field irradiation to the malfunction of CIEDs as well as to deduce the frequency of malfunctions until completion of prostate cancer treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…This can be a reason why fewer secondary neutrons are produced in CIT than in PBT. Also, the previous dosimetric studies suggested that CIT produces fewer secondary neutrons than PBT even for the same physical absorbed dose in Gy [20,26].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This can be a reason why fewer secondary neutrons are produced in CIT than in PBT. Also, the previous dosimetric studies suggested that CIT produces fewer secondary neutrons than PBT even for the same physical absorbed dose in Gy [20,26].…”
Section: Discussionmentioning
confidence: 90%
“…There was no institution which used scanning beams in this study. It has been suggested that scanning particle beam therapy can reduce the secondary neutron volume dramatically [16,17,20,26]. Seidansaal et al have reported that there were no device malfunctions among 32 patients (10 PBT and 22 CIT) with CIED in their investigation [27].…”
Section: Discussionmentioning
confidence: 91%
“…17 Therefore, each patient needs to be considered individually and recognition of the patient's dependence on the CIED identified. If the patient is pacing-dependent, it is usually not recommended to treat them with proton therapy, 45 , 46 , 49 especially in standalone centers with limited resources. Likewise, for the pacing independent patient, risks should be evaluated before delivering proton therapy.…”
Section: Management Of Commonly Seen Implanted Devices In Rt Patientsmentioning
confidence: 99%
“…The wide range of doses that cause failure indicates that there are the differences in dosage depending on the radiation type, the radiation energy, and the radiation quality [ 15 ]. However, the failure that occurs at cumulative dose of ≤1 Gy may be related to neutron-induced disturbances instead of cumulative dose effects [ 16 ]. Therefore, it is considered that CIEDs have a higher risk of failure at cumulative doses >5 Gy, and most guidelines recommend cumulative dose thresholds for CIEDs for patients undergoing radiotherapy [ 4 , 7–10 ].…”
Section: Introductionmentioning
confidence: 99%